Analisis Tingkat Kepuasan Pelanggan Terhadap Pelayanan Coffeeshop (Studi Kasus pada Coffeeshop Bacarito Kopi di Padang) - Putri Rahmania Sari; Suherman Suherman (UNIVERSITAS NEGERI PADANG, 2020)
Abstract —This research was conducted because it has quite high competitiveness of Coffeeshop in Padang so that it is necessary to consider the quality of service which is one way to retain old customers and attract new customers. The quality of service consists of empathy, responsiveness, reliability, tangible and assurance. This studyaaims.to-determine the-level0of customer-satisfaction and service quality-of Coffee Bacarito Coffeeshop. The number of samples=of this-study were 96 customers-from Bacarito Coffee Coffeeshop. The data analysis using the Customer Satisfaction Index (CSI) method. The Customer Satisfaction Index value were obtained 81.87%. The services provided by the Coffee Bacarito Coffeeshop get good overall good overall results so it can be categorized as meeting the expectations of its consumers. This illustrates that Coffeeshop customers are very satisfied with the quality of service performance that Coffeeshop provides. The service that needs to be improved are the responsiveness of employees in dealing with customer complaints, the reliability of Coffeeshop Bacarito Coffee in the open-closed schedule on time, also raise the awareness of customers feedback.Keywords — Customer Satisfaction Index, Coffeeshop Bacarito Kopi, Customer Satisfaction